Digital Texts Support Remote Learning: The Teachers’ and Students’ Perceptions - Andi Tenrisanna Syam; Anis Rifkiani; Rustan Santaria (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
During the Covid-19 pandemic outbreak, the teachers and their students carried out online distance learning by reading text digitally. This study aims to determine the teachers’ and students’ perceptions towards the use of digital text. The writer applied a quantitative qualitative research design. The participants of this study were six teachers from SMAN 2 Luwu and one teacher from SMK Kristen Seriti; 40 students from SMAN 2 Luwu and SMK Kristen Seriti. The participants were selected by using total sampling technique. The instruments were a questionnaire and a structured open-ended interview. The data were analyzed quantitatively and qualitatively. The results showed that the implementation of digital text was less attractive to students. This was evidenced from questionnaire results which showed that 75% of SMAN 2 Luwu students and 45% of SMK Kristen Seriti students think digital text cannot be understood easily than direct explanations from the teacher. However, students assume that they feel challenged to read the digital text without an immediate answer from the teacher. Moreover, the teachers (50%) agreed that digital text is beneficial in delivering material. This study is hoped to give meaningful information for the teachers, students, and further researcher.